Discourse Marker in the Tinker Bell Movie: Sociolinguistic Study - Puspa Putri Ruswina; Puspita Sari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The focus of this research is on the film Tinker Bell's discourse markers. A variety of discourse markers and their purposes are examined in this study, which can be seen in the Tinker Bell movie. In addition, the study explores the differences in speech patterns between male and female language speakers. The "descriptive method" is the approach used in qualitative research. Men and women's dialogue in Tinker Bell's film, together with the reasons for the frequent use of discourse markers and disparities between men and women in their use, were all examined in light of the theory's claimed predictions. According to a number of studies, men and women use and speak different languages and dialects. In Tinkerbell's film, there are a variety of discourse markers, as well as expressive, directed, phatic, and poetic. commissive language functions.